Lung Immune Prognostic Index (Lipi) As Prognostic Markers For Advanced Non-Small-Cell Lung Cancer (Nsclc) Treated With Immunotherapy: A Systematic Review And Meta-Analysis - Delta Iswara; Anggita Dian Karera; Dyah Ati Sayuka; Rachmad Aji Saksana (International Journal of Health Engineering and Technology, 2026)
The Lung Immune Prognostic Index (LIPI), based on the derived neutrophil-to-lymphocyte ratio (dNLR) and lactate dehydrogenase (LDH) levels, has been recognized as an important prognostic biomarker in lung cancer. However, its prognostic value in patients with non–small cell lung cancer (NSCLC) has not been extensively discussed. Objective: This systematic review and meta-analysis aimed to comprehensively evaluate the association between LIPI and survival outcomes in patients with advanced-stage NSCLC receiving immunotherapy. Systematic literature search was conducted across PubMed, ScienceDirect, Cochrane Library, SSRN, Epistemonikos, and Google Scholar databases up to January 10, 2025. Study quality was assessed using the Newcastle–Ottawa Scale (NOS). Data were extracted for qualitative and quantitative synthesis, including pooled analyses and subgroup analyses. Random-effects models were applied to pool hazard ratios (HRs) with 95% confidence intervals (CIs) to assess the association between LIPI and progression-free survival (PFS) and/or overall survival (OS) in patients with advanced NSCLC treated with immunotherapy. A total of 7,551 patients from 13 studies were included in the analysis. Pooled analysis demonstrated that patients with poor or intermediate LIPI scores, compared with those with good LIPI scores, had significantly shorter PFS (HR = 2.20, 95% CI: 1.83–2.63, P < 0.001; HR = 1.47, 95% CI: 1.31–1.65, P < 0.001) and worse OS (HR = 3.31, 95% CI: 2.70–4.06, P < 0.001; HR = 1.88, 95% CI: 1.58–2.23, P < 0.001). Subgroup analyses based on immunotherapy type (monotherapy versus combination therapy) yielded consistent results. This study demonstrates that poor and intermediate LIPI scores are significantly associated with worse prognosis in patients with advanced-stage NSCLC receiving immunotherapy. Therefore, LIPI may serve as a promising non-invasive prognostic biomarker for predicting survival outcomes in this patient population. Keywords: lung immune prognostic index, LIPI, non–small cell lung cancer, immunotherapy.